1997
DOI: 10.1007/s001200050068
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung zur klinischen Relevanz der Acetyliererphänotypisierung bei 196 Urotheltumorpatienten

Abstract: A total of 196 patients with urothelial tumours were phenotyped for N-acetyltransferase 2 by the molar ratio of two caffeine metabolites excreted in urine. The proportion of "slow" acetylators, who are genetically predisposed to urothelial tumours if they have been exposed to aromatic amines in the past, in the entire group was 55%, within the range in a normal population. Among 40 patients with assumed former occupational exposure to aromatic amines, 65% were "slow" acetylators. Invasiveness, histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…A proportion of 82% slow NAT2 acetylators was found within this diseased group. This observation was subsequently confirmed by Golka et al (1996) and Schöps et al (1997), who found 55% slow NAT2 acetylators in an entire group of bladder cancer cases with unspecified exposure, BLADDER CANCER CASES SURVEYED FOR COMPENSATION 907 comparable to the percentage expected for the general population, 52% in bladder cancer cases definitely not occupationally exposed to aromatic amines, but 65% in a subgroup of bladder cancer cases exposed to aromatic amines.…”
supporting
confidence: 61%
“…A proportion of 82% slow NAT2 acetylators was found within this diseased group. This observation was subsequently confirmed by Golka et al (1996) and Schöps et al (1997), who found 55% slow NAT2 acetylators in an entire group of bladder cancer cases with unspecified exposure, BLADDER CANCER CASES SURVEYED FOR COMPENSATION 907 comparable to the percentage expected for the general population, 52% in bladder cancer cases definitely not occupationally exposed to aromatic amines, but 65% in a subgroup of bladder cancer cases exposed to aromatic amines.…”
supporting
confidence: 61%
“…Der Anteil der "langsamen Acetylierer" in der mitteleuropäischen Normalbevölkerung wird mit ca. 50-60% angegeben [19]. [21].…”
Section: N-acetyltransferase 2 (Nat2)unclassified
“…Der Anteil der "langsamen Acetylierer" in der mitteleuropäischen Normalbevölkerung wird mit ca. 50-60% angegeben [22].…”
Section: Abstract: Aromatic Amines -Polycyclic Aromatic Hydrocarbonsunclassified